Weed Management during Pasture Establishment - Brent A. Sellers; Pratap Devkota; Joao Vendramini; Marcelo Wallau; Jason Ferrell (EDIS)
This publication details techniques for chemical weed control prior to and during pasture establishment and is intended for county Extension faculty as well as owners and managers of grazing lands. Written by Brent Sellers, Pratap Devkota, Joao Vendramini, and Marcelo Wallau, and published by the UF/IFAS Agronomy Department, revised August 2021.